Membrane Material-Based Rigid Solar Array Design and Thermal Simulation for Stratospheric Airships - Kangwen Sun; Ming Zhu; Qiang Liu (Advances in Materials Science and Engineering)
In order to improve effective utilization of rigid solar array used in stratospheric airships here, the flexible connection design and light laminated design were introduced to rigid solar array. Based on the analysis of the design scheme, firstly, the equivalent coefficient of thermal conductivity was calculated by the theoretical formula. Subsequently, the temperature variation characteristics of the solar cell module were accurately modeled and simulated by using Computational Fluid Dynamics (CFD) software. Compared to the results of test samples, the solar cell module described here guaranteed effective output as well as good heat insulating ability, effectively improving the feasibility of the stratospheric airship design. In addition, the simulation model can effectively simulate the temperature variation characteristics of the solar cell, which, therefore, provides technical support for the engineering application.